2013
DOI: 10.4172/2329-6836.1000116
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioavailability of Glimepiride in the Presence of Boswellic Acids in Streptozotocin-Induced Diabetic Rat Model

Abstract: The effect of Boswellia serrata standardized extract (BSE) and Boswellic acids (BA) on the pharmacokinetics and pharmacodynamics of glimepiride in normal as well as diabetic rats was studied. In normal and streptozotocin induced diabetic rats the combination of glimepiride with BSE and BA increased all the pharmacokinetic parameters, such as Cmax, AUC0-n, AUCtotal, t½, MRT and decreased the clearance, Vd markedly as compared with the control group. In pharmacodynamic studies, the combination of glimepiride wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Figure 3 portrays the IR spectrum of emodin obtained at the M062x/6-31g (d, p) level of theory, 1 HNMR and 13 CNMR Spectra interpretation for methanol extract. 1 H NMR of the sample (Table 3) contains; 4 sets of aromatic peaks (7.53, 7.23, 7.12 and 6.62), two sets of phenolic peaks (12.12 and 12.06 ) and one set of methyl groups (2.38, attached to aromatic ring) protons. 13 C NMR chemical shift values (Table 4) revealed the presence of; 12 aromatic peaks (166.2, 164.9, 161.8, 148.7, 135.7, 133.4, 124.6, 121.0, 113.9, 109.5, 108.5 and 108.4), 2 carbonyls C (NMR) of the spectra were recorded on NMR machine: JEOL-LA-400 MHz FT-NMR spectrophotometer, at SIPBS, University, Strathclyde, Glasgow, United Kingdom, using deuterated solvents as indicated by Tables 3 and 4.…”
Section: Ftir Spectra Data For Isolated Emodinmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 portrays the IR spectrum of emodin obtained at the M062x/6-31g (d, p) level of theory, 1 HNMR and 13 CNMR Spectra interpretation for methanol extract. 1 H NMR of the sample (Table 3) contains; 4 sets of aromatic peaks (7.53, 7.23, 7.12 and 6.62), two sets of phenolic peaks (12.12 and 12.06 ) and one set of methyl groups (2.38, attached to aromatic ring) protons. 13 C NMR chemical shift values (Table 4) revealed the presence of; 12 aromatic peaks (166.2, 164.9, 161.8, 148.7, 135.7, 133.4, 124.6, 121.0, 113.9, 109.5, 108.5 and 108.4), 2 carbonyls C (NMR) of the spectra were recorded on NMR machine: JEOL-LA-400 MHz FT-NMR spectrophotometer, at SIPBS, University, Strathclyde, Glasgow, United Kingdom, using deuterated solvents as indicated by Tables 3 and 4.…”
Section: Ftir Spectra Data For Isolated Emodinmentioning
confidence: 99%
“…The phenomenon of screening plants for the presence of phyto-molecules of medicinal importance is common place. Natural products have pharmaceutical / pharmacological activity that are useful in treating diseases and are the starting points for drugs discovery from which synthetic drug analogues can be prepared with improved efficacy, potency, safety and purity [1], when isolated, synthetic strategies and tactics are used by organic Chemists providing challenging mechanisms that permit the biologically active product to the target site. A review reported that 577 plant species have been used traditionally due to the secondary metabolites in them, [2 & 3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies, in vivo studies in animal Inhibition of CYP1A2, CYP2C8, CYP2C9, CYP2D6 CYP3A4 (Frank & Unger, 2006) Glimepiride (Samala & Veeresham, 2013) Andrographis paniculata (Kalmegh)…”
Section: Introductionmentioning
confidence: 99%
“…HL-60 cells are mostly used as a cell model to evaluate pharmacological and physiological effects on myeloid differentiation and other aspects. Natural products are comprised of a huge number of chemicals that pose no threat to naturally balanced systems in humans and also act as potential pharmacological agents (11)(12)(13)(14)(15). Naturally occurring Kava plant comprises of different chemical entities including kavalactones.…”
mentioning
confidence: 99%